2020
DOI: 10.1371/journal.pone.0244272
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of COVID-19 patients hospitalized at Clinique Ngaliema, a public hospital in Kinshasa, in the Democratic Republic of Congo: A retrospective cohort study

Abstract: Objectives To describe the clinical characteristics of patients infected with SARS-CoV-2 at Clinique Ngaliema, a public hospital, in Kinshasa, in the Democratic Republic of Congo (DRC). Methods This retrospective study analyzed medical records including socio-demographics, past medical history, clinical manifestation, comorbidities, laboratory data, treatment and disease outcome of 160 hospitalized COVID-19 patients, with confirmed result of SARS-CoV-2 viral infection. Results The median age of patients wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
59
3
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(79 citation statements)
references
References 25 publications
15
59
3
2
Order By: Relevance
“…We examined the full-texts of the remaining 385 articles, resulting in the exclusion of 375 articles due to the following reasons: 192 were review articles; 47 were commentaries, corrections, news items, letters to the editor, short reports, and communications; 43 were in vitro studies; 24 were about COVID-19 only, with non-relevant parameters; 16 were COVID-19 model predictions; 9 were conducted before 2019; 8 were molecular docking studies; 7 were non-relevant case reports; 6 were systematic and scoping reviews; 6 were community implementations; 5 were surveys; 5 were clinical trials related to COVID-19 treatment efficacy/safety but not associated with malaria; 4 were animal studies; 2 were cost-analytic studies; and 1 study reported the data of the same group of participants. After these exclusions, 10 studies [10][11][12][13][14][15][16][17][18][19] met the eligibility criteria and were included. An additional two studies [20,21] were retrieved from Google Scholar and included.…”
Section: Search Resultsmentioning
confidence: 99%
“…We examined the full-texts of the remaining 385 articles, resulting in the exclusion of 375 articles due to the following reasons: 192 were review articles; 47 were commentaries, corrections, news items, letters to the editor, short reports, and communications; 43 were in vitro studies; 24 were about COVID-19 only, with non-relevant parameters; 16 were COVID-19 model predictions; 9 were conducted before 2019; 8 were molecular docking studies; 7 were non-relevant case reports; 6 were systematic and scoping reviews; 6 were community implementations; 5 were surveys; 5 were clinical trials related to COVID-19 treatment efficacy/safety but not associated with malaria; 4 were animal studies; 2 were cost-analytic studies; and 1 study reported the data of the same group of participants. After these exclusions, 10 studies [10][11][12][13][14][15][16][17][18][19] met the eligibility criteria and were included. An additional two studies [20,21] were retrieved from Google Scholar and included.…”
Section: Search Resultsmentioning
confidence: 99%
“…In the first wave of over 60 years, respiratory distress, desaturation (<89%) and severe COVID-19 stage emerged as factors associated with death, while in the second wave it was mainly respiratory distress, desaturation (<89%) and severe stage. Age is no longer associated with mortality as clinicians have drawn particular attention to the elderly as previous studies in the first wave of DRC had already emphasized age as a mortality factor [21][22][23] . Severe stage and desaturation still remain a great challenge in the management of COVID-19, especially when the patient consults late.…”
Section: Discussionmentioning
confidence: 99%
“…In Africa, there is little information available about the clinical characteristics and prognosis of COVID-19-infected patients [4][5][6][7][8]. Global mortality rates range from 4% to 5.6% [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In Africa, there is little information available about the clinical characteristics and prognosis of COVID-19-infected patients [4][5][6][7][8]. Global mortality rates range from 4% to 5.6% [4][5][6][7][8]. In-hospital mortality is high, in particular for patients with acute respiratory distress requiring ICU admission and mechanical ventilation [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation